Evaluation of defect induced surface heterogeneity in Metal-Organic Framework materials with alkali dopants employing adsorption isotherm modelling - Kayal, Sibnath (2022)
In this article, an assessment of surface structural heterogeneity in porous metal organic framework (MOF) structure has been demonstrated by employing the methane and carbon-dioxide adsorption isotherms data. The virgin MIL-101-(Cr) MOF was synthesized by the hydrothermal method and defects were induced in the MOF structure by doping with various alkali (K, Na, Li) cations. The synthesized MOFs were characterized by XRD, SEM, EDX and BET measurement techniques. In order to understand the defect induced surface heterogeneity by alkali cation dopants, the surface energy distributions for CH4 and CO2 adsorptions on MOFs were measured by Dubinin – Astakhov model equation. The surface heterogeneity is mainly controlled by the limiting uptakes of adsorbates, the polarizability of adsorbates and the adsorbate-adsorbent interaction energy.